Anti-Money Laundering / Combating the Financing of Terrorism (AML/CFT) - Ams, Julianne (Selected Legal and Institutional Papers Series; Selected Legal and Institutional Paper ;, 2018)
The Selected Legal and Institutional Papers Series on anti-money laundering and combating the financing of terrorism (AML/CFT) provides a guided summary narrative to the Fund's policy papers on AML/CFT produced over the last twenty years. The paper discusses the context and the foundation of the Fund's AML/CFT program, the enhanced integration of AML/CFT and financial integrity issues into the core work of the Fund, the Fund's AML/CFT capacity development efforts, the emerging financial integrity issues and the future of the Fund's AML/CFT Program.